2018
DOI: 10.1370/afm.2224
|View full text |Cite
|
Sign up to set email alerts
|

Improving Prediction of Dementia in Primary Care

Abstract: PURPOSEThe Mini-Mental State Examination (MMSE) is one of the most widely used instruments to screen for cognitive deficits; however, this instrument alone is not sensitive enough to detect early symptoms of dementia. We aimed to investigate whether additionally using the Visual Association Test (VAT) improves the predictive value of the MMSE score for development of dementia. METHODSAnalyses were based on data from 2,690 primary care patients aged 70 to 78 years who participated in the Prevention of Dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…We found that sex-differences in predictive power of IADL-I may be due to the different distribution of IADL scores in men and women. The median IADL score was somewhat higher in men, and when using Fourth, we adjusted for cognitive functioning using the MMSE, a relatively crude cognitive measure, and the VAT, which has high specificity but low sensitivity for predicting dementia [45]. These could have missed very subtle cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…We found that sex-differences in predictive power of IADL-I may be due to the different distribution of IADL scores in men and women. The median IADL score was somewhat higher in men, and when using Fourth, we adjusted for cognitive functioning using the MMSE, a relatively crude cognitive measure, and the VAT, which has high specificity but low sensitivity for predicting dementia [45]. These could have missed very subtle cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a variable that could represent the change in cognitive functions over time was more desirable. Jongstra et al [ 20 ] reported that the odds ratio of developing dementia was 3.55 (95% confidence interval [CI], 2.51 to 5.00) for elderly populations in primary care who showed a ≥2 point decline in the MMSE score over 2 years. However, according to the study by Hensel et al [ 21 ], changes in the range of 2-4 points over 1.5 years were necessary to conclude that an individual experienced a true change (90% confidence) in MMSE results.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive function declines with age [ 1 ]. This decline is an indicator of lower well-being [ 2 ] and a risk of dementia in the future [ 3 , 4 ]. Considering the growth of the older adult population, it is important to delay or prevent dementia in healthy older adults and older adults with mild cognitive decline [ 5 ].…”
Section: Introductionmentioning
confidence: 99%